Toxic effect of lead (Pb) on hatching rate and larvae abnormalities of Nile Tilapia (Oreochromis niloticus). Issue 1 (February 2021) - Melanie, K; Djamani, R; Zulfahmi, I; Nurlian, R; Sardi, A; Paujiah, E; Muliari, M; Akmal, Y; Humairani, R
Abstract: Like other fish, Nile tilapia ( Oreochromis niloticus ) is one species that potentially exposed to pollutants, including lead (Pb). However, the impact of Pb exposure on hatching rate and larvae development of Nile tilapia is still not investigated. Therefore, this study aimed to examine the toxic effect of Pb exposure on hacthing rate and larvae abnormalities of Nile tilapia. A total of 2, 400 fertilized eggs of Nile tilapia was distributed to control and 3 treatment group namely: treatment A (0.21 mg/L PbCl2 ), treatment B (0.42 mg/L PbCl2 ) and treatment C (0.63 mg/L PbCl2 ) with triplicate. The exposure period lasted for ten days. Cumulative hatching rate, survival rate, malformation rate, heart rate, body length, total lead content and deformities of larvae were analyzed. The results showed that increasing Pb concentration significantly increased malformation rate, heart rate, and total Pb content in Nile tilapia larvae. The highest malformation rate, heart rate and total lead content observed in treatment C were 3.4%, 115.6 beats/minute and 4.80 mg Pb/kg, respectively. Furthermore, Pb was affect several deformities of Nile tilapia larvae including lordosis, kyphosis, and curved tail. Otherwise, exposed to lead up to concentration 0.63 mg/L PbCl2 have no significant effect on cumulative hatching rate, survival rate and body length in Nile tilapia.